ChemInform Abstract: Graphene Oxide as a Recyclable Phase Transfer Catalyst. Issue 42 (1st October 2013) - Kim, Youngmin; Some, Surajit; Lee, Hyoyoung
Abstract Graphene oxide (GO) shows competitive phase transfer catalytic properties in Michael additions to nitroalkenes compared to the established 18‐crown‐6 ether.